2015
DOI: 10.1002/vnl.21466
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal suspension polymerization of vinyl chloride for enhanced productivity

Abstract: In the present study, a mathematical model is developed to numerically predict nonisothermal batch suspension polymerization of vinyl chloride. Free volume theory was used to consider diffusion‐controlled reactions. Model predictions were validated against field data obtained in a pilot scale stirred tank reactor. Variable temperature trajectory was considered during the course of the reaction to improve productivity by reducing the polymerization time for a certain conversion. Variable temperature during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 15 publications
0
48
0
Order By: Relevance
“…The conversion at which the networks formed inside droplets (motionless conversion) can be obtained by the following equation : Xnormalm=Xnormalf1+ρVCMρPVC(ε01ε0) where X f is the critical conversion at which monomer supplied as a separate phase becomes exhausted and can be calculated as a function of the reactor operating condition . The ρVCM and ρPVC represents densities of the monomer and polymer phases, respectively, which are functions of temperature only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion at which the networks formed inside droplets (motionless conversion) can be obtained by the following equation : Xnormalm=Xnormalf1+ρVCMρPVC(ε01ε0) where X f is the critical conversion at which monomer supplied as a separate phase becomes exhausted and can be calculated as a function of the reactor operating condition . The ρVCM and ρPVC represents densities of the monomer and polymer phases, respectively, which are functions of temperature only.…”
Section: Resultsmentioning
confidence: 99%
“…There is no study that exclusively reported the morphology development of S‐PVC at conversions between X m and X f . Among polymerization condition, it was found that the temperature trajectory has a significant effect on the phenomena involved in morphological development . The purpose of the present paper is to introduce an important conversion called X m (motionless conversion) as an inflection point in morphological development through investigating the influence of temperature trajectory on the inner structure of PVC grains.…”
Section: Introductionmentioning
confidence: 97%
“…As compared to resin under constant temperature conditions at 45°C with similar K value, the temperature profile slightly increased the thermal stability of the PVC resin, but greatly changed the macromorphology of resin. Darvishi developed a mathematical model to design the variable temperature trajectory. Adjusts in the temperature trajectory generated a temperature decrease from 68°C to 48°C.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the multi-aspect nature of the rheological properties of the polymer in question, associated with the transition of the granular compound into a viscoplastic state, its relatively high viscosity and sensitivity to heat and shearing, which cause obstacles during processing, must be taken into consideration. [25,26] Considering also the poor dispersibility of nanotubes and their tendency to forming agglomerates, [27] it is justifiable to undertake the investigation of the processability of PVC and nanotubes blends in a molten state using plastographmetry, which could be helpful in determining the technological processing conditions.…”
Section: Introductionmentioning
confidence: 99%